2022
DOI: 10.3390/foods11111542
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Ovalbumin-Induced Food Allergy in Mice by Targeted Rectal and Colonic Delivery of Cyanidin-3-O-Glucoside

Abstract: Targeted rectal and colonic delivery is an effective strategy to exploit the biological functions of polyphenols. This work investigated the anti-food allergy (FA) activity of cyanidin-3-O-glucoside (C3G) delivered by enteric sodium alginate in vivo. The results showed that through targeted rectal and colonic delivery, the C3G showed better results in ameliorating clinical allergic symptoms, diarrhea, and serological indicators including ovalbumin-specific IgE, histamine, and mast cell protease-1. The C3G was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…FAs are dominated by Th2 immune responses and show an imbalance in the Th1/Th2 immune responses. As an important Th2 cytokine, IL-4 can induce IgE release from B cells, activating the degranulation of mast cells, exacerbating allergic reactions, and inhibiting the differentiation and functions of immunosuppressive cells (Treg cells) . In this study, the IL-4 and OVA-IgE levels decreased after fucoxanthin supplementation in allergic mice, inhibiting the Th2 response.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…FAs are dominated by Th2 immune responses and show an imbalance in the Th1/Th2 immune responses. As an important Th2 cytokine, IL-4 can induce IgE release from B cells, activating the degranulation of mast cells, exacerbating allergic reactions, and inhibiting the differentiation and functions of immunosuppressive cells (Treg cells) . In this study, the IL-4 and OVA-IgE levels decreased after fucoxanthin supplementation in allergic mice, inhibiting the Th2 response.…”
Section: Discussionmentioning
confidence: 54%
“…As an important Th2 cytokine, IL-4 can induce IgE release from B cells, activating the degranulation of mast cells, exacerbating allergic reactions, and inhibiting the differentiation and functions of immunosuppressive cells (Treg cells). 47 In this study, the IL-4 and OVA-IgE levels decreased after fucoxanthin supplementation in allergic mice, inhibiting the Th2 response. Furthermore, the levels of the Treg-related IL-10 and TGF-β were increased by the oral administration of fucoxanthin.…”
Section: ■ Discussionmentioning
confidence: 55%
“…However, there was no significant difference in the β-diversity measurements, possibly because of the small sample sizes of both groups or the insufficient treatment cycle of hAMSCs. The analysis using comparison heatmap in genus levels indicated that hAMSCs administration increased the abundance of beneficial bacteria, Odoribacter and Ruminococcus_1 in the intestinal flora, which were short-chain fatty acids (SCFAs) producers with anti-inflammatory properties [ 35 , 36 ]. To identify the underlying dominant bacteria mediated through hAMSCs transplantation, LEfSe analysis was conducted between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanins such as cyanidin 3-O-glucoside increased total β-defensin protein levels in the intestinal mucosa of mice in an ovalbumin-induced food allergy model [ 74 ]. A blueberry powder, high in anthocyanins, supplemented in a high fat diet of rats for 8 weeks significantly increased Defb2 mRNA expression by 2-fold in the ileum compared to rats on a low-fat diet [ 75 ].…”
Section: Regulation Of Host Defense Peptides By Polyphenolsmentioning
confidence: 99%